giai he phuong trinh
x+2\x+1\y=4
1\x^2+1\xy+x\y=3
giai
\(4\sqrt{x+3}+\sqrt{19-3x}=x^2+2x+9\)
\(\hept{\begin{cases}x^3+xy^2=y^6+y^4\\2\sqrt{y^4+1}+\frac{1}{x^2+1}=3-4x^3\end{cases}}\)
Giai hệ phương trình \(\left\{x+y+\frac{1}{x}+\frac{1}{y}=\frac{9}{2}\right\}va\left\{xy+\frac{1}{xy}=\frac{5}{2}\right\}\)
giai he phuong trinh
\(\hept{\begin{cases}x+y+\frac{1}{x}+\frac{1}{y}=\frac{9}{2}\\xy+\frac{1}{xy}+\frac{x}{y}+\frac{y}{x}=5\end{cases}}\)
\(\hept{\begin{cases}x+\frac{1}{x}+y+\frac{1}{y}=\frac{9}{2}\\\frac{1}{4}+\frac{3}{2}\left(x+\frac{1}{y}\right)=xy+\frac{1}{xy}\end{cases}}\)
\(\hept{\begin{cases}x+y+\frac{1}{x}+\frac{1}{y}=\frac{9}{2}\\\frac{1}{4}+\frac{3}{2}\left(x+\frac{1}{y}\right)=xy+\frac{1}{xy}\end{cases}}\)
Giải hệ phương trình
1. x⁴/y² + xy = 72
y⁴/x² + xy = 9
2. x² + (1+y)² = 1
y² +(1+x)² = 1
3. 7 + 2√x - x = (2+√x)√(7-x)
4. √(x+2) - √(3-x) = 2² - 6x + 8
Giải hệ phương trình
1) x⁴/y² + xy = 72
y⁴/x² + xy = 9
2) x² + (1+y)² = 1
y² + (1+x)² = 1
3) 7 + 2√x - x = (2+√x)√(7-x)
4) √(x+2) - √(3-x) = x² - 6x + 8
giai he phuong trinh sau:
a)\(\left(x+\frac{1}{y}\right)+\left(y+\frac{1}{x}\right)=\frac{9}{2}\)
\(\left(x+\frac{1}{y}\right)\left(y+\frac{1}{x}\right)=\frac{9}{2}\)
b)
\(x^2+xy+y^2=7\)
\(x^4+x^2y^2+y^4=21\)